A COMPARATIVE ANALYSIS OF ENGLISH AND UZBEK CHILDREN’S LITERATURE (Ustozlar uchun, 2025)
This article provides a comparative analysis of English and Uzbek children’s literature, focusing on their historical development, thematic content, and cultural values. The study explores how each literary tradition reflects national identity, moral education, and social ideals through stories, characters, and language. While English children’s literature highlights imagination and individualism, Uzbek children’s literature emphasizes morality, respect, and community values.